2017
DOI: 10.1371/journal.pone.0174825
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in progress? A phylogeographic study among populations of Hemitrichia serpula (Myxomycetes)

Abstract: Myxomycetes (plasmodial slime molds, Amoebozoa) are often perceived as widely distributed, confounding to the “everything is everywhere” hypothesis. To test if gene flow within these spore-dispersed protists is restricted by geographical barriers, we chose the widespread but morphologically unmistakable species Hemitrichia serpula for a phylogeographic study. Partial sequences from nuclear ribosomal RNA genes (SSU) revealed 40 ribotypes among 135 specimens, belonging to three major clades. Each clade is domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 61 publications
3
12
0
1
Order By: Relevance
“…Therefore, sequences of the protein elongation factor 1 alpha (EF1A, chromosomal) and the COI gene have been used as markers complementary to SSU. In the few available studies, the patterns obtained were largely congruent with those obtained for the SSU marker (Dagamac et al., ; Feng & Schnittler, ; Feng et al., ; Fiore‐Donno et al., ), and so it seems reasonable to establish the SSU sequence as a DNA marker for ePCR studies. Attempts to develop a marker universal for myxomycetes have failed due to the large divergence between two basal subgroups, called the dark‐ and the bright‐spored myxomycetes (Fiore‐Donno et al., , ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, sequences of the protein elongation factor 1 alpha (EF1A, chromosomal) and the COI gene have been used as markers complementary to SSU. In the few available studies, the patterns obtained were largely congruent with those obtained for the SSU marker (Dagamac et al., ; Feng & Schnittler, ; Feng et al., ; Fiore‐Donno et al., ), and so it seems reasonable to establish the SSU sequence as a DNA marker for ePCR studies. Attempts to develop a marker universal for myxomycetes have failed due to the large divergence between two basal subgroups, called the dark‐ and the bright‐spored myxomycetes (Fiore‐Donno et al., , ).…”
Section: Introductionsupporting
confidence: 61%
“…() found intraspecific differentiation within Lamproderma puncticulatum and L. columbinum using a larger fraction (659 bp) of the SSU gene combined with ITS sequences and EF1A markers. Similarly, intraspecific subclades were found for L. ovoideum (M. Borg Dahl et al., unpublished results), for the bright‐spored species Tubifera ferruginosa (Leontyev et al., ) and Hemitrichia serpula (Dagamac et al., ). In all these cases, scanning electron microscopy images of spores revealed that genetic subclades showed consistent differences in spore ornamentation.…”
Section: Resultsmentioning
confidence: 64%
“…Ecological associations are an important element to contextualise and support biogeographical (i.e. Dagamac et al 2017) or taxonomic (i.e. Walker et al 2015a) studies and to promote applied lines of research on myxomycetes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Тож, хоча ареали цих видів охоплюють різні континенти, вони усюди трапляються лише у рідкісних та вразливих біотопах. Нарешті, по-третє, для деяких видів доведене розділення на географічні раси із суттєво відмінними генофондами (Rojas, Stephenson, 2017;Dagamac et al, 2017), і деякі з цих рас можуть потребувати охорони.…”
Section: вступunclassified